A partition-of-unity based 'FE-Meshfree' hexahedral element with continuous nodal stress. (1st January 2017) - Yang, Yongtao; Chen, Li; Tang, Xuhai; Zheng, Hong; Liu, QuanSheng
Highlights: An 'FE-Meshfree' hexahedral element with continuous nodal stress (Hexa8-CNS) is presented. The derivatives of Hexa8-CNS shape function are continuous at nodes. Hexa8-CNS element is able to achieve nodal stress without any smoothing operation. Comparing to 8-node hexahedral element, the Hexa8-CNS element has high tolerance to mesh distortion. Abstract: A hybrid 'FE-Meshfree' eight-node hexahedral element with continuous nodal stress (Hexa8-CNS) is developed using the concept of partition of unity (PU). One feature of Hexa8-CNS is to achieve continuous nodal stress, meanwhile construct high-order global approximations without adding external node, which leads to high accuracy and convergence rate. Moreover, it is free from the linear dependence problem which cripples many of the PU-based finite elements. Numerical results show that the performance of the element is superior to that of Hexa8 element. Besides, the present element has excellent mesh distortion tolerant capabilities.